Metabolomics study reveals systematic metabolic dysregulation and early detection markers associated with incident pancreatic cancer. Issue 7 (9th December 2021) - Wang, Shuangyuan; Li, Mian; Yan, Li; He, Meian; Lin, Hong; Xu, Yu; Wan, Qin; Qin, Guijun; Chen, Gang; Xu, Min; Wang, Guixia; Qin, Yingfen; et al.
Abstract: Biomarkers for early detection of pancreatic cancer are in urgent need. To explore systematic circulating metabolites unbalance and identify potential biomarkers for pancreatic cancer in prospective Chinese cohorts, we conducted an untargeted metabolomics study in subjects with incident pancreatic cancer and matched controls (n = 192) from the China Cardiometabolic Disease and Cancer Cohort (4C) Study. We characterized 998 metabolites in baseline serum and calculated 156 product‐to‐precursor ratios based on the KEGG database. The identified metabolic profiling revealed systematic metabolic network disorders before pancreatic cancer diagnosis. Forty‐Five metabolites or product‐to‐precursor ratios showed significant associations with pancreatic cancer ( P  < .05 and FDR < 0.1), revealing abnormal metabolism of amino acids (especially alanine, aspartate and glutamate), lipids (especially steroid hormones), vitamins, nucleotides and peptides. A novel metabolite panel containing aspartate/alanine (OR [95% CI]: 1.97 [1.31‐2.94]), androstenediol monosulfate (0.69 [0.49‐0.97]) and glycylvaline (1.68 [1.04‐2.70]) was significantly associated with risk of pancreatic cancer. Area under the receiver operating characteristic curves (AUCs) was improved from 0.573 (reference model of CA 19‐9) to 0.721. The novel metabolite panel was validated in an independent cohort with AUC improved from 0.529 to 0.661. These biomarkers may have a potential value in early detection of pancreatic cancer. Abstract : What's new? Comprehensive metabolite profiling provides new insight into metabolic network dysregulation and non‐invasive biomarkers. This is the first study exploring the associations between nearly 1000 metabolites and pancreatic cancer risk in a prospective multi‐center cohort from China. Our findings highlighted abnormal metabolism of amino acids, steroid hormones, vitamins, and inflammation‐related metabolites. A novel metabolite panel containing aspartate/alanine, androstenediol monosulfate and glycylvaline may have a potential value in early detection of pancreatic cancer.